Active learning in Operations Management: Interactive multimedia software for teaching JIT/Lean Production - Carmen Medina-López; Rafaela Alfalla-Luque; Francisco J. Arenas-Márquez (Journal of Industrial Engineering and Management (JIEM), 2011)
Purpose: Information & Communication Technologies (ICT) can be a fundamental aid for the design of new teaching methods that better adapt to the framework of the European Higher Education Area. In this context, this study aims to develop and assess a complex and truly interactive ICT-based teaching tool for instruction in OM. Design/methodology/approach: A multimedia application for Just-in-Time (JIT) / Lean Production has been conceived, designed and assessed. A constructivist focus was followed in its conception and design to encourage active and flexible learning adapted to each individual's own requirements. Using empirical research the tool has been assessed by students and compared to the traditional teaching methods. Findings: The interactive multimedia application has been clearly valued for the way it conveys information and for its usability, for the way the application is structured and the improvements to students' understanding of the knowledge. Students are also in favour of ICT being incorporated into teaching over more traditional methods. The assessment took students' gender and the average overall mark on their academic records as control variables but, broadly-speaking, no significant differences were found. Research limitations/implications: The study was carried out in a controlled environment and not in the normal on-site university teaching process. Conclusions could be extended to OM and other related subjects, especially if they make use of similar tools to the one described in this paper. Practical implications: This study provides a contribution that allows reflections to be made on the design of specific software for OM and students' perceptions when using it. Originality/value: Through this paper we contribute to an improvement in learning methods in general and to higher education in OM in particular.
Keywords: 650; teaching; operations management; multimedia educational software; just-in-time; lean production